The Impact of Changes in Stock Prices and House Priceson Consumption in OECD Countries - Ludwig, Alexander (IMF Working Papers; Working Paper ;, 2002)
This paper quantifies the different impact of stock and house prices on consumption using data for 16 OECD countries. The analysis finds that the long-run impact of an increase in stock prices and house prices is in general higher in countries with a market-based financial system. The sensitivity of consumption to changes in stock wealth is about twice as large as the sensitivity to changes in housing wealth. Splitting the sample into the 1980s and 1990s shows that both countries with a market-based financial system and countries with a bank-based financial system moved toward a higher degree of responsiveness of consumption to changes in stock prices and house prices.